PENDAMPINGAN LOKAKARYA KOMUNITAS BELAJAR UNTUK PROGRAM SEKOLAH PENGGERAK ANGKATAN 3 DI KABUPATEN MUARA ENIM - Puspita, Desi; Putrawansyah, Ferry; Susanti, Tri; Arif, Alfis (LPPM Universitas Flores, 2024)
Elementary school education units that are part of the driving school program already have a learning community (Kombel). Most school principals and teachers do not fully understand the activities of the learning community in carrying out their duties and roles in supporting the improvement of student learning outcomes. His service aims to improve the competence of educators and build a culture of sustainable learning together through learning communities so that it has an impact on improving student learning outcomes. The method in this learning community workshop starts with opening, starting from oneself, concept exploration, collaboration space, guided reflection, contextual reflection, elaboration of understanding, connection between material, real action, and closing. The activity participants were the principal and 2 teacher representatives from each school consisting of 4 elementary school levels, namely SD Negeri 11 Suhu Dalam, SD Negeri 3 Gumay Talang, SD Negeri 6 Lahat Selatan, and SD IT Abatasa Lahat. The final product of this learning community workshop is a plan for activities to develop a sustainable learning community in schools.